Acute Retinal Necrosis: Clinical Features, Diagnostic Pitfalls, Treatment, and Outcome of an Insidious Disease in Children. Case Report and Review of the Literature - Chiara Mapelli; Paolo Milella; Caterina Donà; Marco Nassisi; Marco Nassisi; Silvia Osnaghi; Francesco Viola; Francesco Viola; Carlo Agostoni; Carlo Agostoni; Francesca Minoia; Giovanni Filocamo (Frontiers Media S.A., 2022)
ObjectiveThis study aims to explore clinical features, diagnostic work-up, treatment, and outcomes of pediatric patients with acute retinal necrosis (ARN), and to propose a standardized management of this condition in childhood.MethodsClinical manifestations, diagnostic work-up, and treatment of three pediatric cases with ARN were analyzed. Furthermore, a review of the literature was performed from January 1990 to November 2021, focused on 1) clinical presentation; 2) differential diagnosis, including both infectious and non-infectious conditions; 3) key role of diagnostic techniques; and 4) currently available treatments.ResultsData from 72 children with ARN (69 from literature and 3 from our center) were analyzed. The most frequent presenting symptoms were red eye resistant to topical treatment (57%) and altered vision (58%), 25 patients had bilateral involvement. In 30% a known history of herpetic infection was reported. PCR testing on anterior chamber and/or vitreous sampling was performed in 46 cases (64%) and was diagnostic in 88% of them, with herpes simplex virus (HSV) 2 being the most frequently identified pathogen (57%). All patients underwent systemic antiviral therapy (16% only oral); adjunctive intravitreal injections were performed in 21% of them.ConclusionsARN is a rare but severe ocular infection presenting as a panuveitis with occlusive retinal vasculitis and peripheral retinal necrosis. Varicella-zoster virus and HSV 1-2 are most frequently implicated. Due to a high incidence of rhegmatogenous retinal detachment and optic atrophy, ARN has a poor prognosis with a potentially severe impact on visual function. Although a prompt recognition is crucial to prevent complications, ARN diagnosis in children is still challenging.